Icebreaker Propulsion System Simulation. Phase IV. The Design and Predicted Performance of a Propulsion System for the M-13 Icebreaker - Lewis, Jack W.; Lecourt, Everett J. (1968)
A feasible design of the main propulsion system for the M-13 icebreaker is presented in this final report of a four phase study. Procedures are described that were used in meeting given performance specifications covering open water and icebreaking, operations and maneuvers. The automatic controls necessary to meet the performance specifications are developed. Results of the steady-state design analysis and dynamic performance analysis are presented, and an overall evaluation including major conclusions is included. (Author) See also Phase 3, AD-845 525.